Arrhythmias after the Fontan procedure. Issue 8 (August 1992) - Peters, Nicholas S; Somerville, Jane
Abstract : Objective —To study the determinants and outcome of arrhythmias after the Fontan type operation. Design —Retrospective analysis of data in patients operated on between 1972 and 1986 (follow up 5–19 years (mean 12 years)). Patients —All 60 patients undergoing a Fontan type procedure at the National Heart Hospital, London, during the study period (mean age (SD) 12·3 (6·8) years). Results —Postoperative arrhythmias occurred in 34 patients (57%), and 11 (58%) of 19 early postoperative deaths (within seven days) were related to arrhythmias. Early arrhythmias occurred in 19 (32%) patients of whom 11 (58%) died. All patients with early atrial fibrillation and His bundle tachycardia died and only preoperative atrial fibrillation recurred early. There was a higher incidence of early arrhythmias, which were less well tolerated, in double inlet single ventricle patients (9/19) than in those with tricuspid atresia (8/37). There were no other preoperative determinants of early arrhythmias or deaths from early arrhythmia. Late (after seven days) arrhythmias occurred in 15 (37% of hospital survivors). They had higher right atrial (RA) pressures both early and late after operation and had lower ventricular ejection fractions late after operation. Of those with atrial arrhythmias 86% had RA obstruction and 57% had an RA thrombus or pulmonary embolism at presentation; this was also confirmed in two patients in whom late sudden deaths occurred. Atrial fibrillation early after reoperation for RA obstruction was fatal. The actuarial arrhythmia free survival for hospital survivors was 60% at 10 years. Conclusions —Early postoperative arrhythmias were poorly tolerated, particularly atrial fibrillation and His bundle tachycardia. Previous atrial fibrillation was a relative contraindication to this procedure. Late postoperative arrhythmias were associated with higher RA pressures measured both early and late after operation and worse late ventricular function. Late arrhythmias may be the first manifestation of RA obstruction, which must be sought. RA thrombus was common in patients with atrial arrhythmias and should be treated early with anticoagulants.